2017
DOI: 10.1097/sla.0000000000001841
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Heterotopic Ossification Early After Burn Injuries

Abstract: This HO risk scoring system identifies high-risk burn patients suitable for diagnostic testing and interventional HO prophylaxis trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…[7] The incidence of HO ranges from 0.2% to 5.6% in burn injury patients. [812] In this mass casualty incident, the incidence of elbow HO in the burn patients treated in our institution was 3.6% (2/56).…”
Section: Discussionmentioning
confidence: 90%
“…[7] The incidence of HO ranges from 0.2% to 5.6% in burn injury patients. [812] In this mass casualty incident, the incidence of elbow HO in the burn patients treated in our institution was 3.6% (2/56).…”
Section: Discussionmentioning
confidence: 90%
“…Risk factors can be etiologically specific: the degree of spasticity in spinal cord injury (SCI) patients, need for prolonged mechanical ventilation in patients with severe burns, and surgical approach for orthopedic procedures all prove to be prominent predictive factors for HO development [11,87–89]. A number of these factors have been incorporated into scoring systems used to predict HO development with successful results in burn patients [90]. In most cases, however, these predictive factors are insufficient to dictate treatment algorithms, highlighting the need for early and accurate diagnosis before lesions are formed.…”
Section: The Evolving Practice Of Diagnosis and Treatmentmentioning
confidence: 99%
“…Records were reviewed, and all individuals were assigned a risk score for the development of HO using a previously validated scoring system. 15 The HO Risk Scoring System, derived using the Burn Model Systems National Database and externally validated, assigns point values based on burn size and deep wounds to the upper extremities, trunk, and head and neck. All subjects with a HO risk score of ≥7 were included.…”
Section: Retrospective Review Of Human Experiencementioning
confidence: 99%
“…The authors found that burn size, and need for autografting to the arms, head or neck, and trunk were predictors of HO development. 15 Estrogens and androgens have been well characterized for their role in postnatal bone development, especially in the obstetrics and gynecology literature in the context of postmenopausal decreases in trabecular and cortical bone after loss of these steroids 16,17 corroborated by mouse models of orchiectomy/ovariectomy. 18,19 It is this association between steroids and their pro-osteogenic 20 and metabolic effects that serves as the rationale for extended oxandrolone therapy in burn patients who are at risk for osteo-and sarcopenia during their hospital course and recovery.…”
mentioning
confidence: 99%